EEG alpha reactivity on eyes opening discriminates patients with schizophrenia and schizoaffective disorder - Garakh, Zhanna; Larionova, Ekaterina; Shmukler, Alexander; Horáček, Jiří; Zaytseva, Yuliya (Clinical neurophysiology, 2024)
OBJECTIVE: Alpha activity in the electroencephalogram (EEG) is typically dominant during rest with closed eyes but suppressed by visual stimulation. Previous research has shown that alpha-blockade is less pronounced in schizophrenia patients compared to healthy individuals, but no studies have examined it in schizoaffective disorder. METHODS: A resting state EEG was used for the analysis of the alpha-reactivity between the eyes closed and the eyes opened conditions in overall (8 - 13 Hz), low (8 - 10 Hz) and high (10 - 13 Hz) alpha bands in three groups: schizophrenia patients (SC, n = 30), schizoaffective disorder (SA, n = 30), and healthy controls (HC, n = 36). All patients had their first psychotic episode and were receiving antipsychotic therapy. RESULTS: A significant decrease in alpha power was noted across all subjects from the eyes-closed to eyes-open condition, spanning all regions. Alpha reactivity over the posterior regions was lower in SC compared to HC within overall and high alpha. SA showed a trend towards reduced alpha reactivity compared to HC, especially evident over the left posterior region within the overall alpha. Alpha reactivity was more pronounced over the middle and right posterior regions of SA as compared to SC, particularly in the high alpha. Alpha reactivity in SC and SA patients was associated with various negative symptoms. CONCLUSIONS: Our findings imply distinct alterations in arousal mechanisms in SC and SA and their relation to negative symptomatology. Arousal is more preserved in SA. SIGNIFICANCE: This study is the first to compare the EEG features of arousal in SC and SA.
Keywords: Female; schizofrenie; lidé středního věku; Electroencephalography; Alpha Rhythm; mužské pohlaví; oči; psychotické poruchy; mladý dospělý; Humans; dospělí; elektroencefalografie; Psychotic Disorders; lidé; Middle Aged; Schizophrenia; Eye; ženské pohlaví; Young Adult; alfa rytmus EEG; Adult; Male